Assessing the Efficacy and Safety of Tirofiban in Combination With Dual-antiplatelet Therapy in Progressive Ischemic Stroke Patients. Issue 3 (September 2021) - Zhang, Haiqi; Lin, Feng; Zhao, Yanjun; Chang, Wansheng; Liu, Hui; Yin, Jijun; Li, Long
Abstract : Abstract: This study assessed the efficacy and safety of tirofiban in combination with dual-antiplatelet therapy (DAPT) in progressive ischemic stroke. One hundred and four patients equally divided into a tirofiban group or DAPT group were enrolled from June 2018 to December 2019. Efficacy outcomes included National Institutes of Health Stroke Scale score for 14 days, and modified Rankin scale (mRs) scores as excellent (mRs 0–1) or favorable (mRs 0–2) measured 90 days after stroke. At 14 days, the tirofiban group had a lower National Institutes of Health Stroke Scale score compared with the DAPT group (F = 14.959, P = 0.000). The mRS scores of the 2 groups at 90 days after treatment were significantly different from those before treatment. At 90 days, excellent favorable functional outcome (mRS ⩽ 2) was achieved in 33 of 52 (63.43%) patients in the tirofiban group compared with 25 of 52 (48.08%) patients in the DAPT group. The incidence of bleeding was 5.77% in the tirofiban group, compared with 0% in DAPT group. Intravenous (IV) tirofiban alone or combined with DAPT was shown to be safe and effectively improved clinical outcome in progressive ischemic stroke patients. IV tirofiban was shown to be superior to the DAPT regimen.